Strategies to combat antimicrobial resistance in hospital infections: A literature review (Research, Society and Development, 2024)
Antimicrobial resistance (AMR) in hospital infections represents a critical challenge for global public health, compromising treatment efficacy and increasing morbidity and mortality. This article reviews existing literature on strategies to combat AMR in hospital settings. Key approaches include the implementation of antimicrobial stewardship programs, which promote the rational use of antibiotics, and the continuous education of healthcare professionals on appropriate prescribing practices. Rigorous surveillance and infection control are essential to identify and contain outbreaks of resistant pathogens. The development of new therapies, including antibiotics and non-antibiotic alternatives, is crucial to address AMR. Research in rapid diagnostics is also vital to ensure appropriate and timely treatment. Collaboration among healthcare institutions, governments, and international organizations is fundamental to effectively monitor and respond to AMR. This study highlights the need for a multifaceted and coordinated approach to combat antimicrobial resistance in hospital infections, integrating education, surveillance, therapeutic innovation, and global cooperation.